2013
DOI: 10.1007/s12028-013-9818-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Neurocritical Care Service without a Dedicated Neuro-ICU on Quality of Care in Intracerebral Hemorrhage

Abstract: Introduction of a neurocritical service without a neuro-ICU at our institution was associated with a trend toward longer ICU LOS and improvement in some key metrics of quality of care for patients with ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…The impact of neurocritical care/neuro-intensivists’ care on outcomes in patients with life-threatening neurological and neurosurgical illnesses has been reported by various authors [ 90 95 ]. In particular, the proven efficacy of a neurointensivist-managed neurocritical/intensive care unit for patients with aneurysmal SAH has been frequently reported.…”
Section: Reviewmentioning
confidence: 99%
“…The impact of neurocritical care/neuro-intensivists’ care on outcomes in patients with life-threatening neurological and neurosurgical illnesses has been reported by various authors [ 90 95 ]. In particular, the proven efficacy of a neurointensivist-managed neurocritical/intensive care unit for patients with aneurysmal SAH has been frequently reported.…”
Section: Reviewmentioning
confidence: 99%
“…Studies have shown that a neurointensivist managing a NSICU improves outcomes and shortens length of stays in all neurocritically ill patients and also improves documentation [ 5 9 ]. Similar improvements after dedicated neurointensivists have been demonstrated in patients with ischemic stroke [ 9 14 ], subarachnoid hemorrhage [ 15 , 16 ], traumatic brain injury [ 17 , 18 ], intracerebral hemorrhage [ 19 ], and neuromuscular respiratory failure [ 20 ]. These studies, however, lack information on patient and family satisfaction concomitantly with the improvement in other clinical quality metrics.…”
Section: Introductionmentioning
confidence: 61%
“…Their role is important for the patient’s health and clinical outcomes [ 35 , 36 ]. Studies have shown that neurointensivists who manage NSICUs improve outcomes and documentation and shorten the length of stay of all neurocritically ill patients [ 37 41 ], including those suffering from ischemic stroke [ 41 46 ], subarachnoid hemorrhage [ 47 , 48 ], traumatic brain injury [ 49 , 50 ], intracerebral hemorrhage [ 51 ], and neuromuscular respiratory failure [ 52 ].…”
Section: Adaptive Immunity (Fig 3 )mentioning
confidence: 99%